Analysis of PANoptosis-Related LncRNA-miRNA-mRNA Network Reveals LncRNA SNHG7 Involved in Chemo-Resistance in Colon Adenocarcinoma - Huang, Jingjing; Jiang, Shiyao; Liang, Lu; He, Hua; Liu, Yueying; Cong, Li; Jiang, Yiqun (Frontiers in Oncology, 2022)
Colon adenocarcinoma (COAD) is one of the most common malignancies, and its metastatic lesions are the leading cause of death in COAD patients. PANoptosis is a recently identified pathway for programmed cell death implicated in developing COAD. Long non-coding RNAs (lncRNAs) are key regulators of cancer occurrence and progress. Although their function has captured much attention in COAD, the relationship between COAD metastasis-associated lncRNA expression and PANoptosis remains elusive. Therefore, this study aimed to explore the potential regulatory roles of metastasis- and PANoptosis-associated lncRNAs in COAD. Nine lncRNAs associated with metastasis and PANoptosis in COAD were identified from The Cancer Genome Atlas (TCGA) and GEO databases. Their functions were analyzed by multiple bioinformatics methods, and the lncRNA-miRNA-mRNA network was constructed. Multivariate Cox analysis identified one lncRNA (SNHG7) significantly related to COAD prognosis. Subsequent analyses showed its expression correlated with tumor stage and lymph node metastasis. Moreover, drug sensitivity analysis and in vitro experiments suggest that lncRNA SNHG7 contributes to drug resistance in COAD. In summary, lncRNA SNHG7 is a potential target for diagnosing and treating COAD and plays a crucial role in regulating apoptosis, metastasis, and drug resistance in COAD.